Ookinete-Specific Genes and 18S SSU rRNA Evidenced in Plasmodium vivax Selection and Adaptation by Sympatric Vectors - González-Cerón, Lilia; Rodríguez, Mario H.; Ovilla-Muñoz, Marbella T.; Santillán-Valenzuela, Frida; Hernández-Ávila, Juan E.; Rodríguez, María Carmen; Martínez- Barnetche, Jesús; Villarreal-Treviño, Cuauhtémoc (Frontiers in Genetics, 2020)
In the southern Pacific coast of Chiapas, Mexico (SM), the two most abundant vector species, Nyssorhynchus albimanus and Anopheles pseudopunctipennis, were susceptible to different Plasmodium vivax Pvs25/28 haplotypes. To broaden our understanding of the existing P. vivax in the area, genes encoding for proteins relevant for ookinete development and the 18S rRNA were studied P. vivax infectivity (percentage of infected mosquitoes and oocyst numbers) was evaluated by simultaneously feeding infected blood samples from patients to Ny. albimanus and An. pseudopunctipennis female mosquitoes. Three infectivity patterns were identified: one group of parasites were more infective to An. pseudopunctipennis than to Ny. albimanus, another group was more infective to Ny. albimanus, while a third group infected similarly both vectors. In 29 parasite isolates the molecular variations of ookinete-specific genes and the 18S rRNA-type S were analysed. Using concatenated sequences, phylogenetic trees and Structure analysis parasite clustering within SM isolates and between, these and those from other geographical origin were investigated. A ML phylogenetic tree resolved two parasite lineages: PvSM-A and PvSM-B. They were associated to a different 18S rRNA variant. PvSM-A parasites had 18S rRNA variant rV2 and correspond to parasites causing high oocyst infection in Ny. albimanus. A new ML tree and Structure analysis, both comprising global sequences showed PvSM-A clustered with Latin American parasites. While, all isolates of PvSM-B had 18S rRNA variant rV1 and remained as a unique genetic cluster comprising two subgroups: PvSM-Ba, producing high infection in An. pseudopunctipennis and PvSM-Bb causing similar oocyst infection in both vector species. PvSM-A parasites were genetically similar to parasites from South America. While PvSM-B were exclusive of southern Mexico, and compart ancestry with Asian parasites. The results suggest that these lineages evolved separately, likely by geographic and vector restriction.